Gene expression and TNF-alpha secretion profile in rainbow trout macrophages following exposures to copper and bacterial lipopolysaccharide - Teles, M. (2019)
Fish macrophage function can be altered after exposure to pathogens as well as to xenobiotics. Considering that wild and farmed fish can be exposed in their habitats simultaneously to different types of stressors, including chemical contaminants (e.g. heavy metals) and pathogens (e.g. bacteria), it is fundamental to study their impact either isolated or in combination. Therefore, the present study aimed to evaluate the effects of copper and bacterial lipopolysaccharide (LPS), alone and in combination, on the transcription of target genes related with immune system, respiratory burst activity and cell death, using rainbow trout macrophages as in vitro model. A cell viability experiment was performed to determine the sub-lethal concentrations of copper for rainbow trout macrophages and the LC50-24 h was estimated at 60 μM. The expression of proinflammatory cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumour necrosis factor-α (TNFα) increased after copper and copper plus LPS exposure. Copper and LPS interact positively inducing an increase in cytokine expression, which may be indicative of an increased inflammatory response. However, the increase in TNFα mRNA expression induced by 50 μM copper was not accompanied by protein secretion indicating that mRNA abundance does not always reflect the level of protein and that the translation of the TNFα mRNA is somehow inhibited. Serum amyloid A (SAA) and trout C-polysaccharide binding protein (TCPBP) mRNA expression also increased after copper, LPS or LPS plus copper exposure, indicating a role of acute phase proteins in the local response to inflammation. NADPH oxidase and glutathione peroxidase gene expression increased in macrophages after 24 h exposure to copper, LPS or LPS plus copper. The results from the present study improve the understanding of mechanisms involved in copper toxicity, as well as the interaction with a simulated-inflammatory process.